Legal Policy in the Regulations for the Sale of State Houses Class III (Idle State Property) Without Auction to Occupants/State Servants Reviewed From the Perspective of “The Theory of Justice” From John Rawls - Herman CS Sudira; Suhariningsih; Moh. Fadli; Iwan Permadi (Budapest International Research and Critics University, 2022)
Auctions are universally believed to be the most accountable and fair trading system. This is also recognized by the Republic of Indonesia in administering the state treasury and the Management of State Property, where all sales of State Property must be carried out through auctions. The problem is, there is a legal Politics (legal policy) of differential treatment (